Planning and evaluating technical cooperation between the Caribbean Food and Nutrition Institute and its member countries 1999-2003 (CFNI KingstonJM, 2003)
Evaluates and reports on technical cooperation between CFNI and its member countries during the period under review.
Keywords: TECHNICAL COOPERATION